Real-time PCR for detection of Streptococcus suis serotype 2 in cerebrospinal fluid of human patients with meningitis. - Nga, T; Nghia, H; Tu, L; Diep, T; Mai, N; Chau, T; Sinh, D; Phu, N; Nga, T; Chau, N; Campbell, J; Hoa, N; et al. (2011)
Streptococcus suis serotype 2 is an emerging zoonotic pathogen and is the main cause of acute bacterial meningitis in adult patients in Vietnam. We developed an internally controlled real-time PCR for detection of S. suis serotype 2 in cerebrospinal fluid (CSF) samples targeted at the cps2J gene. Sensitivity and specificity in culture-confirmed clinical samples were 100%. The PCR detected S. suis serotype 2 infection in 101 of 238 (42.4%) prospectively collected CSF samples, of which 55 (23%) were culture positive. Culture-negative but PCR-positive CSF samples were significantly associated with the use of antimicrobial agents before admission. S. suis serotype 2 infection was more common than infections with Streptococcus pneumoniae and Neisseria meningitidis combined. Our results strikingly illustrate the additional diagnostic value of PCR in patients who are pretreated with antimicrobial agents and demonstrate the extremely high prevalence of S. suis infections among Vietnamese adult patients with bacterial meningitis.